Seagrasses in the age of sea turtle conservation and shark overfishing - Heithaus, Michael R.; Alcoverro, Teresa; Arthur, Rohan; Burkholder, Derek A.; Coates, Kathryn A.; Christianen, Marjolijn J. A.; Kelkar, Nachiket; Manuel, Sarah A.; Wirsing, Aaron J.; Kenworthy, W. Judson; Fourqurean, James W. (Frontiers in Marine Science, 2014)
Efforts to conserve globally declining herbivorous green sea turtles have resulted in promising growth of some populations. These trends could significantly impact critical ecosystem services provided by seagrass meadows on which turtles feed. Expanding turtle populations could improve seagrass ecosystem health by removing seagrass biomass and preventing of the formation of sediment anoxia. However, overfishing of large sharks, the primary green turtle predators, could facilitate turtle populations growing beyond historical sizes and trigger detrimental ecosystem impacts mirroring those on land when top predators were extirpated. Experimental data from multiple ocean basins suggest that increasing turtle populations can negatively impact seagrasses, including triggering virtual ecosystem collapse. Impacts of large turtle populations on seagrasses are reduced in the presence of intact shark populations. Healthy populations of sharks and turtles, therefore, are likely vital to restoring or maintaining seagrass ecosystem structure, function, and their value in supporting fisheries and as a carbon sink.